2020
DOI: 10.3390/vision4010011
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements and Fixation-Related Potentials in Reading: A Review

Abstract: The present review is addressed to researchers in the field of reading and psycholinguistics who are both familiar with and new to co-registration research of eye movements (EMs) and fixation related-potentials (FRPs) in reading. At the outset, we consider a conundrum relating to timing discrepancies between EM and event related potential (ERP) effects. We then consider the extent to which the co-registration approach might allow us to overcome this and thereby discriminate between formal theoretical and compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 138 publications
0
20
0
Order By: Relevance
“…For instance, FRPs have already been useful in testing the ecological validity of parafoveal ERP and EM effects unrelated to semantic processing (e.g., Degno et al, 2019a, 2019b; Hutzler et al, 2013; Niefind & Dimigen, 2016; for a review, see Degno & Liversedge, 2020). Experimental conditions where previews and targets are visually different show greater processing costs when compared to conditions where previews and targets are identical, a preview effect related to display change frequently reported in EM research (see Schotter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, FRPs have already been useful in testing the ecological validity of parafoveal ERP and EM effects unrelated to semantic processing (e.g., Degno et al, 2019a, 2019b; Hutzler et al, 2013; Niefind & Dimigen, 2016; for a review, see Degno & Liversedge, 2020). Experimental conditions where previews and targets are visually different show greater processing costs when compared to conditions where previews and targets are identical, a preview effect related to display change frequently reported in EM research (see Schotter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of FRPs through a co‐registration set‐up provides some important advantages. For instance, both FRP and EM data together may discern between different types of processing that cause either distinct or comparable disruption to both data streams (for a review, see Degno & Liversedge, 2020). Additionally, FRPs have already been successfully combined with the boundary paradigm in word pair or word lists reading experiments exploring semantic parafoveal processing (Antúnez et al, 2021; Dimigen et al, 2012; López‐Pérez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This interference has been shown in many gaze-contingent studies in which reading performance is reduced when words are manipulated in the parafovea 17,[49][50][51] . Fixation or event-related potentials based on EEG is another method used in reading studies [52][53][54][55] , and have shown different brain activity patterns for different word presentation rates, addressing the importance of using natural reading paradigms 56 . While fixation-related potentials method has provided important insights by demonstrating a lexical frequency effect for foveal word recognition on the N1 component 38,39 , it has failed to provide conclusive results with regard to parafoveal lexical processing 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…These paradigms have produced a wealth of data, which are the foundation for influential models of visual word recognition (Balota et al, 2007; Carreiras, Armstrong, Perea, & Frost, 2014; Norris, 2009). However, several authors have pointed out that RSVPs lack essential features of natural reading that can significantly affect the word recognition process, the most important ones being parafoveal preview and saccade-related attention shifts (Degno & Liversedge, 2020; Dimigen, Sommer, Hohlfeld, Jacobs, & Kliegl, 2011; Hutzler et al, 2007; Kornrumpf, Niefind, Sommer, & Dimigen, 2016; Rayner, 1998; Weiss, Knakker, & Vidnyanszky, 2016).…”
Section: Introductionmentioning
confidence: 99%